2020
DOI: 10.1111/aji.13386
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of placental ischemia‐stimulated natural killer cells causes a preeclampsia‐like phenotype in pregnant rats

Abstract: Problem:The Reduced Uterine Perfusion Pressure (RUPP) rat model of placental ischemia recapitulates many characteristics of preeclampsia including maternal hypertension, intrauterine growth restriction (IUGR), and increased cytolytic natural killer cells (cNKs). While we have previously shown a 5-fold higher cytotoxicity of RUPP NKs versus normal pregnant NKs, their role in RUPP pathophysiology remains unclear.In this study, we tested the hypotheses that (1) adoptive transfer of RUPP-stimulated NKs will induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…[53][54][55] Activated NK cells can induce production of anti-angiogenic factors, resulting in decreased placental vascularization and contributing to FGR. [56][57][58] While AT1-AA can activate the AT1 receptor, 59 they can also target cells for destruction through antibody dependent cellular cytotoxicity (ADCC), which involves activated NK cells. In ADCC, an antigen is bound by an antibody's binding region, while the constant region of the antibody can be recognized by NK cells, which induce apoptosis of the targeted cell.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Activated NK cells can induce production of anti-angiogenic factors, resulting in decreased placental vascularization and contributing to FGR. [56][57][58] While AT1-AA can activate the AT1 receptor, 59 they can also target cells for destruction through antibody dependent cellular cytotoxicity (ADCC), which involves activated NK cells. In ADCC, an antigen is bound by an antibody's binding region, while the constant region of the antibody can be recognized by NK cells, which induce apoptosis of the targeted cell.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that Reduced Uterine Perfusion Pressure (RUPP) promoted the activation and proliferation of cNK cells, and that NK cell removal ameliorated hypertension, fetal growth restriction, and inflammation ( 127 ). Adoptive transfer of NK cells from RUPP to normal pregnant rats resulted in NK cell stimulation, increased uterine artery resistance index (UARI) and oxidative stress reaction in the placenta, which ultimately caused PE and IUGR ( 128 ). RUPP acceptors of NK cells from normal pregnant rats exhibited normal NK activation, plasma soluble fms-like tyrosine kinase receptor-1 (sFlt1), plasma and decidual VEGF, and normal UARI, thereby compromising hypertension and fetal growth restriction ( 128 ).…”
Section: Dnk Cells In Pementioning
confidence: 99%
“…Adoptive transfer of NK cells from RUPP to normal pregnant rats resulted in NK cell stimulation, increased uterine artery resistance index (UARI) and oxidative stress reaction in the placenta, which ultimately caused PE and IUGR ( 128 ). RUPP acceptors of NK cells from normal pregnant rats exhibited normal NK activation, plasma soluble fms-like tyrosine kinase receptor-1 (sFlt1), plasma and decidual VEGF, and normal UARI, thereby compromising hypertension and fetal growth restriction ( 128 ). The studies point out that cNK cells matter in the pathogenesis of PE, while normal NK cells alleviate hypertension and promote fetal development ( 128 ).…”
Section: Dnk Cells In Pementioning
confidence: 99%
See 1 more Smart Citation
“…These activated NK cells also produce TNF-α and INF-γ further contributing to the chronic inflammation in PE [42,97]. Recent studies from Travis et al [57,98] show that NK cells stimulated from the RUPP rat model of PE can cause preeclamptic symptoms in healthy pregnant rats and that NK cells from PE rats have a 5-fold increase in cytolytic activity compared to normal controls. Furthermore, B cells secrete AT1-AA which directly activate the AT1R resulting in increased vascular resistance but also producing anti-angiogenic factors downstream of AT1R activation.…”
Section: Nk Cells In Preeclampsiamentioning
confidence: 99%